2011
DOI: 10.1002/pssa.201127020
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study on the structural, phonon, and thermodynamic properties of the ternary carbides in Ti–Al–C system

Abstract: The structural, phonon, and thermodynamic properties of the ternary carbides Ti2AlC, Ti3AlC, and Ti3AlC2 in the Ti–Al–C system are investigated by using first‐principles calculations in this paper. Phonon dispersion curves and partial density of states have been investigated and revealed the different Ti–C bond characteristics between Ti3AlC and the two other compounds. The Gibbs energy, entropy, heat capacity, and thermal expansion coefficient of the three compounds are predicted by means of the quasi‐harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Figure 8A shows the free energy versus temperature plot with similar characteristics wherein the free energy decreases gradually with increasing temperature. This behavior is due to the fact that both the internal energy and entropy increases with temperature, which leads to a decrease in the free energy 44 . Also, the inspection of the free energy plots depicts that flower-like MoS 2 nanostructures are thermodynamically stable in the studied temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8A shows the free energy versus temperature plot with similar characteristics wherein the free energy decreases gradually with increasing temperature. This behavior is due to the fact that both the internal energy and entropy increases with temperature, which leads to a decrease in the free energy 44 . Also, the inspection of the free energy plots depicts that flower-like MoS 2 nanostructures are thermodynamically stable in the studied temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, due to technological advances such calculations are rapidly becoming practically feasible, and in recent years several MAX phase related theoretical studies dealing with temperature dependence have been published. While most of these studies have been dedicated to the characterization of thermodynamic properties such as heat capacity, thermal expansion, and bulk modulus [14][15][16][17][18], some of them have indeed focused on phase stability. However, their scopes have been limited to investigations of the relative stability between α and β MAX phase polymorphs [19][20][21].…”
mentioning
confidence: 99%
“…Although 2D titanium carbides seem to exhibit special crystal structures and morphologies, they are also closely related to the synthesis processes of 3D titanium carbide particles, which can be seen in the thermodynamic calculation of Al-Ti-C system [74,75]. For instance, the first step of the reaction with Al, Ti and C with specific ratios and synthetic parameters will form Ti n+1 AlC n ( n = 2 or 3), which are the precursor phases (named MAX) mentioned previously.…”
Section: The Synthesis and Characterization Of Two-dimensional Titmentioning
confidence: 99%
“…It isinexpensive and has good stability, while its average size is relatively large. In previous studies, graphite particles of approximately 5 μm, 15 μm, 38 μm or even 48 μm were reported as used to fabricate TiC [30,75,80,86]. Becasuse graphite has a large size, it always becomes a residual phase in the reactant and has not been completely reacted with Ti, except for via some special measures [81].…”
Section: The Synthesis and Characterization Of Three-dimensional Tmentioning
confidence: 99%